Poems and essays - Ransom, John Crowe, 1888-1974 (Vintage book ;, 1955)
A selection of forty-four lyrics and eight substantial essays from the author's complete works. Ransom, long one of America's eminent critics, writes perceptively of literature and politics in these essays.